Mindfulness Therapy as an Intervention to Address Overthinking - Savero, Andhika Rayhan; Prianggi Amelasasih (Universitas Negeri Medan, 2025)
Overthinking is a form of psychological pressure that is common in the work environment and can have a negative impact on employee performance and well-being. This study aims to explore the effectiveness of mindfulness therapy in reducing symptoms of overthinking in HR employees at PT. X. The research uses an experimental qualitative approach with a One Group Pretest-Posttest design. The subjects consisted of two employees who were selected purposively because they showed symptoms of overthinking. The intervention was carried out in ten sessions using deep breathing and self-talk techniques. Data were collected through pretest-posttest (15 yes/no items), semi-structured interviews, and documentation. Data analysis was conducted using a descriptive thematic approach to identify change patterns in participants’ experiences, and supported by statistical analysis using the Wilcoxon Signed-Rank Test to assess differences in scores before and after the intervention. The results indicated that both participants experienced a reduction in overthinking symptoms following the therapy. Although the Wilcoxon test showed no statistically significant result (p = 0.180), the direction of change consistently reflected improvement. The study concludes that mindfulness therapy has potential as an effective psychological intervention in the workplace context.